Penmanship: Teaching and Supervision - Hiles, Leta Severance (Salt Lake City, UT : Project Gutenberg, 2021)
"Penmanship: Teaching and Supervision" by Leta Severance Hiles is an educational manual written in the early 20th century. The book aims to address the fundamental aspects of teaching and supervising penmanship, highlighting the need for both legibility and efficiency in writing skills. It covers the importance of correct posture, muscular movement, and the tools needed for effective penmanship instruction. The opening of the work establishes the significance of penmanship within the educational framework, arguing that writing is often overlooked despite its crucial role in a child's learning experience. Hiles points out common problems like illegible handwriting and poor posture among students, emphasizing that these issues cause significant long-term disadvantages. She introduces a structured approach that educators can adopt, suggesting practical solutions and techniques to improve writing skills, illustrating the connection between fine motor skills and overall educational success. The introduction sets the stage for a comprehensive guide on effective penmanship instruction grounded in health, practicality, and educational theory. (This is an automatically generated summary.)
Release date is 2021-11-05
Craig Kirkwood and the Online Distributed Proofreading Team at https://www.pgdp.net (This file was produced from images generously made available by The Internet Archive)
Keywords: Penmanship